A comprehensive guide to the management of anaemia. Issue 9 (22nd October 2019) - Boyce, Sara
Abstract : A systematic approach to evaluation and investigation is key to the successful management of anaemia. This article examines the classification of anaemia, its underlying causes and clinical manifestations, and the range of treatments available.